In vivo Imaging Technologies to Monitor the Immune System - McCarthy, Claire E.; White, Jordan M.; Viola, Nerissa T.; Gibson, Heather M. (Frontiers in Immunology, 2020)
The past two decades have brought impressive advancements in immune modulation, particularly with the advent of both cancer immunotherapy and biologic therapeutics for inflammatory conditions. However, the dynamic nature of the immune response often complicates the assessment of therapeutic outcomes. Innovative imaging technologies are designed to bridge this gap and allow non-invasive visualization of immune cell presence and/or function in real time. A variety of anatomical and molecular imaging modalities have been applied for this purpose, with each option providing specific advantages and drawbacks. Anatomical methods including magnetic resonance imaging (MRI), computed tomography (CT), and ultrasound provide sharp tissue resolution, which can be further enhanced with contrast agents, including super paramagnetic ions (for MRI) or nanobubbles (for ultrasound). Conjugation of the contrast material to an antibody allows for specific targeting of a cell population or protein of interest. Protein platforms including antibodies, cytokines, and receptor ligands are also popular choices as molecular imaging agents for positron emission tomography (PET), single-photon emission computerized tomography (SPECT), scintigraphy, and optical imaging. These tracers are tagged with either a radioisotope or fluorescent molecule for detection of the target. During the design process for immune-monitoring imaging tracers, it is important to consider any potential downstream physiologic impact. Antibodies may deplete the target cell population, trigger or inhibit receptor signaling, or neutralize the normal function(s) of soluble proteins. Alternatively, the use of cytokines or other ligands as tracers may stimulate their respective signaling pathways, even in low concentrations. As in vivo immune imaging is still in its infancy, this review aims to describe the modalities and immunologic targets that have thus far been explored, with the goal of promoting and guiding the future development and application of novel imaging technologies.